Integrasi Perhitungan BMI dan TDEE pada Aplikasi Pemantauan Gaya Hidup Sehat - Ulya Nidaul; Irma Handayani (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to evaluate the performance of a healthy lifestyle monitoring application integrated with Body Mass Index (BMI) and Total Daily Energy Expenditure (TDEE) calculations. The evaluation focuses on three primary aspects: usability using the System Usability Scale (SUS), adherence through usage consistency monitoring, and effectiveness through pre–post statistical analysis. The study involved 30 respondents for usability assessment and 30 participants for adherence measurement and statistical testing. The findings show that the application demonstrates excellent usability with an SUS score of 82.4. User adherence reached 63.3%, surpassing the minimum target set for the study. Additionally, the statistical test resulted in p = 0.003, indicating a significant difference between pretest and posttest conditions. These results suggest that the application provides a positive user experience, maintains user engagement, and has a measurable impact on users’ understanding and behavior in monitoring their health status and daily energy needs.